Biodegradation of waste PET based copolyesters in thermophilic anaerobic sludge. (January 2015) - Hermanová, Soňa; Šmejkalová, Pavla; Merna, Jan; Zarevúcka, Marie
Abstract: A series of poly(ethylene terephthalate- co -lactate) copolyesters with random microstructure was prepared from PET waste beverage bottles andl -lactic acid. Square specimens, sectioned from melt-pressed film, were incubated in thermophilic sludge (55 °C, alkaline environment) for 394 days. The biodegradability of the samples, determined from biogas yield, reached 34–69 % depending on the starting aromatic to aliphatic units' ratio. Water uptake study in sludge and abiotic buffers at 55 °C showed sharp border around 57% of aromatic units in copolyester composition between polymers susceptible and resistant to both hydrolytic attack by hydrolases and the abiotic hydrolysis. Samples biodegraded in sludge and those abiotically aged in buffers were characterized by 1 H NMR, ATR-FTIR, SEC, DSC, and TGA analysis to gain an insight into the chain scission mechanism. Aromatic oligomers as model of copolyester degradation intermediates were prepared and proved to biodegrade in sludge as well.